PENGENDALIAN PROSES PRODUKSI BAHAN PAKAN BUNGKIL SAWIT DALAM PERSPEKTIF KEAMANAN PANGAN - Legis Tsaniyah; Hermawan Hermawan (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Palm kernel cake (Palm Kernel Expeller - PKE) is one of the feed rawmaterials are abundant in Indonesia. PKE material very easily covered with mold,so the opportunity to produce mycotoxins, one of which is Aspergillus Sp. whichproduces aflatoxin. Aflatoxins are toxic not only cattle, but also the residue isstored in animal products such as meat and milk. The concentration of aflatoxin inanimal feed under the provisions of the Indonesian National Standards Bodyshould not exceed 100 mg / kg. The concentration of aflatoxin allowed to enterthe human food ingredient according to the provisions of the WHO maximumppb.Pengendalian 0:03 PKE production process by using GMP + and HACCP isone of the most logical alternative and effective current to the prevention ofaflatoxin. The HACCP system is implemented following the 12 steps and 7principles of implementation of Codex Alimentarius Commission asrecommendations.Keywords: Palm Kernel Expeller, Food Safety in Animal Feed, HACCP system